ACCESSIBILITY MODEL FOR MICRO AND SMALL ENTERPRISES IN OBTAINING UMK CAPITAL FINANCING FROM FINANCIAL INSTITUTIONS IN ACEH PROVINCE, INDONESIA - Any Meilani, Yasrizal, RiniFebrianti, Etty Puji Lestari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the international economy, small and medium-sized enterprises ( MSMEs) play an important role. Micro and small entrepreneurs still dominate Aceh's economic sector. KUR aims to improve and expand bank services to active MSEs, increase the competitive capacity of MSEs, encourage economic growth and labor absorption, and alleviate poverty. The data analysis model in this study is In Aceh Province, in the binary logit model multiple regression analysis method, the number of SMEs studied was 110. Research results show that company characteristics, financial characteristics, collateral requirements, and Small Business Support Service have a major impact on access to financial institutions, while ownership features are not relevant. Another factor in the inaccessibility of SMEs to financial institutions is that they are mostly influenced by those SME owners who only increase their funding resources. Some UKM owners' understanding of Islamic law and usury often affect access to conventional financial institutions.